Behaviour of high strength reinforced concrete beam with metakaolin under static loading - Amer, Yusuff (2005)
The need of cement replacement material (CRM) in reinforced concrete has gained its popularity among the researchers to produce a high strength concrete (HSC) for structural engineering application. This paper presents the experimental results of the static loading effect on reinforced concrete beam with metakaolin (MK7003). Three different percentages, 5%, 10% and 15% of MK7003 were incorporated as CRM in reinforced concrete beam, and 0% of MK7003 as the control specimen. Eight no of beams, with dimension of 1400mm x 150mm x 125mm, were tested, two for each different percentages and two beams as control specimens. The beams were subjected to four point loading test until failure. The findings of the experiment been shown that the structural performance were improved with the inclusion of MK7003. The observation made suggested that MK7003 with 10% replacement gave the optimum performance of the reinforced concrete.